2017
DOI: 10.4103/ccd.ccd_426_17
|View full text |Cite
|
Sign up to set email alerts
|

Management of broken dental implant abutment in a patient with bruxism: A rare case report and review of literature

Abstract: This rare case report describes prosthodontic complications resulting from a dental implant was placed surgically more distally in the area of the missing mandibular first molar with a cantilever effect and a crest width of >12 mm in a 59-year-old patient who had a history of bruxism. Fracture of abutment is a common complication in implant was placed in area with high occlusal forces. Inability to remove the broken abutment may most often end up in discarding the implant. Adding one more dental implant mesial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…It has been reported that habits such as bruxism are risk factors of abutment fracture in patients with dental implants. 18 In this regard, there is a possibility that Ti, and one-and two-piece ZAs are more susceptible to display modes of fractures comparable to the patterns reported in the present in-vitro investigation. It is speculated that individuals demonstrating high-biting forces and simultaneously exposed to risk factors of implant failure (such as those mentioned above) more often display Ti and one-and two-piece ZA fractures compared with unexposed patients with normal biting forces.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that habits such as bruxism are risk factors of abutment fracture in patients with dental implants. 18 In this regard, there is a possibility that Ti, and one-and two-piece ZAs are more susceptible to display modes of fractures comparable to the patterns reported in the present in-vitro investigation. It is speculated that individuals demonstrating high-biting forces and simultaneously exposed to risk factors of implant failure (such as those mentioned above) more often display Ti and one-and two-piece ZA fractures compared with unexposed patients with normal biting forces.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, normal periodontal tissue does not form around the implants. Implants that directly contact the alveolar bone may fracture the implant fixture portion when the periodontal ligament fails to disperse the occlusal forces transmitted from the teeth (Al‐Almaie, 2017; Murakami et al, 2020). The mechanical strength of metal and ceramic implants also differs significantly from that of bone (Bonfield & Grynpas, 1977).…”
Section: Problems With and Limitations Of Current Dental Implant Trea...mentioning
confidence: 99%